2015
DOI: 10.1186/s12864-015-2067-2
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing reveals genomic heterogeneity and antibiotic purification in Mycobacterium tuberculosis isolates

Abstract: BackgroundWhole genome sequencing has revolutionised the interrogation of mycobacterial genomes. Recent studies have reported conflicting findings on the genomic stability of Mycobacterium tuberculosis during the evolution of drug resistance. In an age where whole genome sequencing is increasingly relied upon for defining the structure of bacterial genomes, it is important to investigate the reliability of next generation sequencing to identify clonal variants present in a minor percentage of the population. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
3
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 36 publications
7
53
3
2
Order By: Relevance
“…The majority of the detected sequence heterogeneity therefore resulted from an abundance of rare alleles in the population—approximately 80% of the total heterogeneity was accounted for by v-SNPs with a frequency of less than 20%. This degree of variation is higher than reported previously [5456] and shows that MTBC might explore its mutational space to a greater extent than previously thought. Importantly, the intra-patient SFS was very similar to the inter-host SFS reported by Pepperell and colleagues [57], suggesting that forces shaping the diversity at the host population level are already prominent within patients, before the bottleneck of transmission.
Fig.
…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…The majority of the detected sequence heterogeneity therefore resulted from an abundance of rare alleles in the population—approximately 80% of the total heterogeneity was accounted for by v-SNPs with a frequency of less than 20%. This degree of variation is higher than reported previously [5456] and shows that MTBC might explore its mutational space to a greater extent than previously thought. Importantly, the intra-patient SFS was very similar to the inter-host SFS reported by Pepperell and colleagues [57], suggesting that forces shaping the diversity at the host population level are already prominent within patients, before the bottleneck of transmission.
Fig.
…”
Section: Resultscontrasting
confidence: 62%
“…In a recent report of a detailed sampling of MTBC populations across several foci of infection within deceased TB patients, Lieberman et al [56] showed a large genetic diversity within each patient that may not be completely represented in tracheal aspirates—a proxy the authors used for sputum samples. Furthermore, several studies found a comparable degree of genetic diversity of MTBC within and between hosts [42, 54, 59]; these observations complement radiological findings of granuloma dynamics [14]. In the majority of these studies, authors comment on the transience of the detected polymorphisms and highlight the importance of sampling the host population as fully as possible.…”
Section: Discussionmentioning
confidence: 72%
“…We suspect that it is possible that PI treatment provided a strong selection for the emergence of glpK mutants in these mice. Variants with glpK frameshift mutations are detectable in sputum samples from many human TB patients and, furthermore, these glpK mutants were unstable (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of genetically variable drug‐resistant bacterial populations within a single patient is now acknowledged and could affect drug resistance evolution (Black et al., 2015; Eldholm et al., 2014; Müller, Borrell, et al., 2013; Shamputa et al., 2004). Meacci et al.…”
Section: Intra‐host Genetic Variability Of Drug‐resistant Populationsmentioning
confidence: 99%
“…The intra-host evolution of bacterial resistance patterns is one of the key aspects of drug resistance emergence and spread (Eldholm et al, 2014;Meacci et al, 2005;Merker et al, 2013). The existence of genetically variable drug-resistant bacterial populations within a single patient is now acknowledged and could affect drug resistance evolution (Black et al, 2015;Eldholm et al, 2014;Müller, Borrell, et al, 2013;Shamputa et al, 2004). Meacci et al investigated M. tu-berculosis population evolution in a noncompliant patient during more than 12 years of active disease.…”
Section: Intr A-hos T G Ene Ti C Variab Ilit Y Of Drug -Re S Is Tanmentioning
confidence: 99%